Teacher Education in the 21st Century - Botshabeng Monyai, Reginald (IntechOpen, 2019)
A learner-centred curriculum provides space for the learner to be actively involved in knowledge production and learning. Such can only happen if the learner's confidence is boosted by a feeling of control and ability to manage his or her progress towards acquiring a qualification. The twenty-first century teacher must create an environment that not only supports the Four Pillars of Learning but also leads to learners being allowed a voice to ask pertinent questions. The teacher should be able to guide the student to full physical and mental maturity and should help to develop critical thinking, and the students should be encouraged to practice the truth and have self-respect and respect for other people. This can happen if the learner is afforded the opportunity to self-accept. If the learners fail to do so, they are likely to have lack of confidence, which will lead to lack of independence.